Nutritional Parameters in Colostrum of Different Mammalian Species - Paolo Polidori; Roberta Rapaccetti; Yulia Klimanova; Jing-Jing Zhang; Giuseppe Santini; Silvia Vincenzetti (Beverages, 2022)
Colostrum (or first milk) is the food produced by all the mothers in all specific mammalian species, ruminants, monogastric and marine mammalians for their newborns during the first 24–48 h post-partum. Colostrum provides to the neonate all essential nutrients necessary for the first week of life, but the effect of colostrum shows a long-term effect not limited to these first days. Colostrum is considered to be a safe and essential food for human consumption. Some young children can show at the beginning of their colostrum-based diet some side effects, such as nausea and flatulence, but they disappear quickly. In human colostrum, the immunoglobulins and lactoferrin determined show the ability to create natural immunity in newborns, reducing greatly the mortality rate in children. Recent studies suggest that bovine colostrum (BC) may be an interesting nutraceutical food, due to its ability in preventing and/or mitigating several diseases in newborns and adults. This review aims to show the nutraceutical and functional properties of colostrum produced by several mammalian species, describing the different colostrum bio-active molecules and reporting the clinical trials aimed to determine colostrum nutraceutical and therapeutic characteristics in human nutrition.